Gastroesophageal Reflux Disease in Obesity - Hotmen Sijabat; Marcellus Simadibrata; Murdani Abdullah; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Incidence of gastroesophageal reflux disease (GERD) has been significantly increased, and nearly 25% of the population has experienced GERD. It appears to be correlated to an increasing number of obesity in the population (BMI 30 kg/m2). Mechanism of the GERD is affected by multifactor. Increased intra-abdominal pressure is considered as one of risk factors for GERD. The development of GERD is virtually associated with a down turning of lower esophageal sphincter tonus, increased transient lower esophagus sphincter relaxation (TLESR), and decreased capacity of esophageal clearance. Management of GERD in obesity includes weight loss treatment, pharmacotherapy by using prokinetics, H2 -receptor antagonists, proton pump inhibitor and surgical approach including fundoplication, gastric banding and vertical banded gastroplasty. Keywords: GERD, obesity, BMI, TLESR, weight loss, abdominal pressure